Sulfonated Poly(ether sulfone)-Based Catalyst Binder for a Proton-Exchange Membrane Fuel Cell - Krishnan, N. Nambi; Kim, Hyoung-Juhn; Jang, Jong Hyun; Lee, Sang-Yeop; Cho, EunAe; Oh, In-Hwan; Hong, Seong-Ahn; Lim, Tae-Hoon (WILEY, 2009)
Sulfonated poly(ether sulfone) copolymer (PES 60) and its partially fluorinated analogue (F-PES 60) were synthesized via the nucleophilic aromatic polycondensation of commercially available monomers to make a polymer electrolyte membrane and a binding material in the electrodes of a membrane-electrode assembly (MEA). PES 60 and F-PES 60 showed proton conductivities of 0.091 and 0.094 S/cm, respectively, in water at room temperature. The copolymer was dissolved in the mixture of alcohol and water to get a 1 wt%, binder solution. A catalyst slurry was prepared with the copolymer solution and sprayed on the copolymer (PES 60 or F-PES 60) membrane to obtain a MEA. Both PES 60 and F-PES 60 based MEAs were fabricated with different amounts of their binder in the electrodes to examine the effect of the copolymer binder in the catalyst layer on the fuel cell performance. The MEA with 2 wt% copolymer binder in the electrodes showed the best fuel cell performance. 20119 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2499-2506, 2009
Keywords: POLYMER ELECTROLYTE; ETHER KETONE); HIGH-TEMPERATURE; PERFORMANCE; COPOLYMERS; PERMEATION; CONDUCTION; IMPEDANCE; LAYER